Massive Blooms of Chattonella subsalsa Biecheler (Raphidophyceae) in a Hypereutrophic, Tropical Estuary—Guanabara Bay, Brazil - Viana, Tatiana V.; Fistarol, Giovana O.; Amario, Michelle; Menezes, Rafael B.; Carneiro, Beatriz L. R.; Chaves, Daisyane M.; Hargreaves, Paulo I.; Silva-Lima, Arthur W.; Valentin, Jean L.; Tenenbaum, Denise R.; Arruda, Edilson F.; Paranhos, Rodolfo; et al. (Frontiers in Marine Science, 2019)
Cell concentrations of the potentially harmful raphidophyte Chattonella subsalsa Biecheler were quantified in surface waters of Guanabara Bay, a heavily eutrophicated estuarine system in tropical Brazil, from February 2014 to January 2018. Cells were imaged and quantified in live samples by means of an automated imaging system (FlowCam®). Bloom episodes (>0.1 × 106 cells L−1) were observed in 37 samples, mostly in a shallow (<10 m) area with extremely high nutrient and organic matter loads (average total P = 19 μM and total N = 344 μM), intermediate salinity (average 24.5), and low water transparency (average Secchi depth = 0.54 m) due to continental runoff. Blooms in this area reached up to 13.3 × 106 cells L−1. C. subsalsa cell concentration was correlated with parameters linked to eutrophication of the bay. On a monthly basis, C. subsalsa abundance was correlated with a period of positive Multivariated El Niño/Southern Oscilation Index (MEI) that lasted from the beginning of 2015 to mid-2016 (known as Godzilla El Niño), indicating a potential influence of regional climate on the occurrence of C. subsalsa. Notably, at least six fish kill episodes were reported in the Bay during this period which, added to the toxicity of C. subsalsa strains isolated from the bay to Artemia nauplia (48h-LC50 = 7.3 × 106 cells L−1), highlights the threat that this HAB species poses to the environment. This is the first report of recurrent, massive C. subsalsa blooms in Guanabara Bay. Regardless of the influence of climatic forcing in favoring C. subsalsa development, reducing nutrient loads would be the best strategy to mitigate blooms of this and other potentially harmful algae in Guanabara Bay.